Gentamicin resistance in clinical strains of Enterobacteriaceae associated with reduced gentamicin uptake - Adwan, K; Abu-Hasan, N (Folia microbiologica, 1998)
Seven strains of Enterobacteriaceae resistant to gentamicin obtained as representatives of the predominant resistance profiles in the clinical laboratories of Rafeidia and Al-Watani Hospitals in Nablus (Palestine) were included. Five strains showed a broad aminoglycoside resistance profile but contained no evidence of gentamicin acetylation, adenylation, or phosphorylation. Gentamicin uptake in two tested strains was significantly reduced, compared to that of gentamicin-sensitive E. coli (MIC, 0.5 microgram/mL). These strains are likely resistant due to a relative reduction of the amount of gentamicin and other aminoglycosides entering the bacterial cell. Two strains showed evidence of adenyltransferase ANT(2")-I activity.
Keywords: Microbial Sensitivity Tests; enterobakteriální infekce; gentamiciny; Humans; antibiotická rezistence; mikrobiální testy citlivosti; Escherichia coli; lidé; Enterobacteriaceae Infections; antibakteriální látky; plazmidy; Gentamicins; Proteus; Enterobacteriaceae; Anti-Bacterial Agents; Klebsiella; Drug Resistance, Microbial; Plasmids; Providencia